FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN DISCHARGE PLANNING OLEH PERAWAT PADA PASIEN POST SECTIO CAESAREA DI RUANG ALSTONIA DAN RUANG VATICA RUMAH SAKIT EKA HOSPITAL PEKANBARU - Azita, Riza; Kasih Bratha, Shinta Dewi; Rajagukguk, Sartika; Draini, Osi (Ensiklopedia of Journal, 2024)
Abstractt: Discharge planning the planning of going back of the patient, and give  information to elient and their family, about something the necessary to avoid and  to do rete his or her condition. This study aim to determine the facor associated with implementation of discharge planning.The design of this study was cross sectionalusing the Chi-square test. The sample is 35 implementing nurse. The sampling technique use  total sampling. This research was conducted at Eka Hospital Pekanbaru in Juy and Agustst 2023. The researche instrumen uses questionnaies and documents/patient status. The result of the study show that there is a relationship betwen knowledge factors and the implementation of discharge planning (0,011), there is relationship betwen attitude factors and the implementation of discharge planning (0,044) and there is relationship betwen motivasional factors and the implementation of discharge planning (0,002). The result of this study recomended the need for formal educationm discharge planning training for nurse competence in implementing discharge planning and monitoring regulary and continuously evaluation of hospital.Keywords: Discharge Planning, Knowledge, Motivation, Attitude